AdipoRon Engages Microglia to Antinociception through the AdipoR1/AMPK Pathway in SNI Mice. (10th April 2023) - Fang, Qian; Li, Jie; Wang, Yaping; Liu, Xinli; Shi, Yu; Chen, Jiali; Zhan, Hongrui; Zeng, Yanyan; Wu, Wen
Abstract : Background . Microglia-associated neuroinflammation plays a crucial role in the initiation and development of neuropathic pain (NeuP). AdipoRon is an analog of adiponectin that exerts an anti-inflammatory effect in various diseases through the adiponectin receptor 1 (AdipoR1) signaling mechanism. Adenosine monophosphate-activated protein kinase (AMPK) is a downstream target of AdipoR1, and the AdipoR1/AMPK pathway is involved in the regulation of inflammation. This study is aimed at investigating whether AdipoRon could alleviate NeuP by inhibiting the expression of microglia-derived tumor necrosis factor-alpha (TNF- α ) through the AdipoR1/AMPK pathway. Methods . In vivo, the NeuP model was established in mice through the spared nerve injury. The von Frey test was used to detect the effect of AdipoRon on the mechanical paw withdrawal threshold. Western Blot was performed to detect the effects of AdipoRon on the expression of TNF- α, AdipoR1, AMPK, and p-AMPK. Immunofluorescence was performed to observe the effects of AdipoRon on spinal microglia. In vitro, lipopolysaccharide (LPS) was used to induce inflammatory responses in BV2 cells. The effect of AdipoRon on cell proliferation was detected by CCK-8. qPCR was used to examine the effects of AdipoRon on the expression of TNF- α and polarization markers. And the effect of AdipoRon on the AdipoR1/AMPK pathway was confirmed by Western Blot. Results . Intraperitoneal injection of AdipoRon alleviated mechanical nociception in SNI mice, and the application of AdipoRon reduced the expression of TNF- α and the number of microglia in the ipsilateral spinal cord. Additionally, AdipoRon decreased the protein level of AdipoR1 and increased the protein level of p-AMPK in the ipsilateral spinal cord. In vitro, AdipoRon inhibited BV2 cell proliferation and reversed LPS-induced TNF- α expression and polarization imbalance. Furthermore, AdipoRon reversed the LPS-induced increase in AdipoR1 expression and decrease in p-AMPK expression in BV2 cells. Conclusions . AdipoRon may alleviate NeuP by reducing microglia-derived TNF- α through the AdipoR1/AMPK pathway.